Minimally invasive left-sided esophagectomy (MILO): a novel approach for locally advanced tumors of the gastroesophageal junction. Issue 1 (27th June 2020) - Gossage, J A
Summary: Recent national audit has shown that levels of minimally invasive esophagectomy for cancer have increased to around 45% in the UK. The hybrid approach is the most common, with a laparoscopic abdominal phase and an open thoracic dissection. A number of centers have now adopted a two-phase Ivor–Lewis minimally invasive esophagectomy using a laparoscopic abdominal phase, followed by a thoracoscopic chest phase with a mini-thoracotomy to extract the specimen. The two-phase nature of the procedure lengthens the operative time and makes returning to the abdominal cavity difficult. The thoracotomy incision can also be painful and may reduce respiratory function post operatively. This report describes a novel single-phase minimally invasive left-sided technique with a mini-laparotomy for specimen extraction. This method offers excellent hiatal exposure, avoids a thoracotomy, and shortens the procedure time. Minimally invasive left-sided esophagectomy is a new useful approach for tumors located at the gastroesophageal junction.